Program Bimbingan Dan Konseling Komprehensif - Muhammad Syahrul; Martini Martini; Andi Bunyamin (JURKAM: Jurnal Konseling Andi Matappa, 2022)
Guidance and counseling services in schools is to support students in achieving the maturity of personality, social skills, academic skills, and leads to the formation of individual career maturity that can be useful in the future. Amanat Permendiknas 27 tahun 2008 is directed that counselor has competence in developing comprehensive guidance and counseling program, but  some  counselors do to design a comprehensive  program, Subjects of this study consist of students, teachers, subject teachers, parents and committee. This study use the Research and Development (R & D) methode. Direct technique of data collection through interviews, documentation and assessment scale studies. The results of the research, guidance and counseling teachers do not understand the concept of comprehensive guidance and counseling. Conclusion the results of the study, model of comprehensive guidance and counseling conditions of school in Indonesia development, of the effective before preparing guidance and counseling programs, guidance and counseling teachers This model is become a reference it will be developed in several advanced research such as testing the effectiveness of the program model.